Reviews. Issue 3 (1st December 2015) - Ray, Marcie; Cooper, Tom; Lindberg, Julianne
BUILDING THE OPERATIC MUSEUM: EIGHTEENTH-CENTURY OPERA IN FIN-DE-SIÈCLE PARIS, WILLIAM GIBBONS (2013) Rochester, NY: University of Rochester Press, xii+267 pp., ISBN: 9781580464000, h/bk, 85.00ACTING THROUGH SONG: TECHNIQUES AND EXERCISES FOR MUSICAL-THEATRE ACTORS, PAUL HARVARD (2013) London: Nick Hern Books, 275 pp., ISBN: 9781848422292, p/bk, £12.99WE'LL HAVE MANHATTAN: THE EARLY WORK OF RODGERS AND HART, DOMINIC SYMONDS (2015) Oxford: Oxford University Press, 332 pp., ISBN: 9780199929481, h/bk, 34.95